The Effect of Need for Uniqueness on Word of Mouth - Cheema, Amar; Kaikati, Andrew M. (Journal of Marketing Research, 2010)
This research examines the psychosocial cost associated with positive word of mouth (WOM), which can decrease the uniqueness of possessions and thus harm high-uniqueness consumers (pilot study). As a result, high- (versus low-) uniqueness consumers are less willing to generate positive WOM for publicly consumed products that they own. However, high uniqueness does not decrease willingness to generate WOM for privately consumed products (Study 1). Study 2 demonstrates that for publicly consumed products, WOM that includes positive recommendations is more persuasive than WOM that only contains product details. Consequently, the effect of uniqueness is more pronounced for WOM recommendations than for WOM that only provides details (Study 3). Study 4 confirms that high- (versus low-) uniqueness consumers are less willing to recommend a public product to others but are equally willing to discuss product details. Study 5 analyzes real-world WOM content and finds evidence in support of these results.